Effects of Thai traditional massage to anxiety, depression and pain level of patients with myofascial pain syndrome at the Clinic of Applied Thai Traditional Medicine, Faculty of Medicine, Thammasart University. - Naewboot , J.; Kanchanatawan, B. (Chulalongkorn Medical Journal, 2023)
Background : Myofascial pain syndrome is chronic pain that mainly occurs in the middle age or young working population. Psychological factors, stress, anxiety and sadness and other factors are supposed to affect the severity of the disease. Thai massage is one of the treatments expected to have both physical and mental effects. Objective : To study the effects of Thai massage on the levels of anxiety, depression and pain in patients with myofascial pain syndrome at the Clinic of Applied Thai Traditional Medicine , Faculty of Medicine, Thammasart University. Design : Quasi-experimental research (pre-post study in one group) Setting : Clinic of Applied Thai Traditional Medicine, Faculty of Medicine, Thammasat University. Materials and Methods : The study was performed on 20 patients with myofascial pain syndrome who received Thai massage at the Clinic of Applied Thai Traditional Medicine, Faculty of Medicine, Thammasat University. Three consecutive sessions of Thai massage were operated performed on all patients. To determine the effect of treatment, all subjects were evaluated the levels of anxiety and depression and pain level both before and after 3 sessions of Thai massage; paired t-test and Wilcoxon, singed rank test were applied to analyze the data. Results : The patients with myofascial pain syndrome got significantly lower scores of anxiety, depression and pain level after receiving 3 sessions of Thai massage. The average scores of anxiety were 10.60 and 5.53 at pre-treatment and post treatment , consecutively. The average scores of depression were 8.4 and 4.5 at pretreatment and post treatment, consecutively. The average scores of pain were 2.46 and 1.8 at pre-treatment and post treatment, consecutively. Conclusion : Thai massage can be treatment that significantly reduce anxiety, depression and pain level in myofascial pain syndrome significantly.